Fintech Developments in Indonesia: A Critical Multiperspective Analysis Review - Fitria Marisya; Marsinah Marsinah; Rolia Wahasusmiah (Universitas 45 Surabaya, 2025)
This research analyzes fintech development in Indonesia through a multi-perspective bibliometric approach that includes technology, regulation, economy, and social impact. Using scientific publication data from several leading databases, the study identified key trends, dominant keywords, and collaboration networks between researchers. The results show that technologies such as blockchain, big data, and artificial intelligence are the main drivers of fintech transformation. At the same time, adaptive regulation is needed to support innovation while protecting consumers. In addition, fintech has contributed significantly to financial inclusion, especially for people whom traditional banking services have not reached. However, challenges such as low digital financial literacy and lack of public trust must be overcome through integrated education and policies. The study offers strategic recommendations to strengthen an inclusive and sustainable fintech ecosystem. It opens up opportunities for further research on the long-term impact and adoption of new technologies in the fintech ecosystem in Indonesia.